Prevalence and pattern of intimate partner violence among men and women in Edo State, Southern Nigeria - Tijani I.A. Oseni; Tawakalit O. Salam; Temitope Ilori; Mojeed O. Momoh (African Journal of Primary Health Care & Family Medicine, 2022)
Background: Intimate partner violence (IPV) is a growing concern in Nigeria and globally. Although women are at greater risk of IPV, men are also affected, but this is less reported.